MECHANISMS OF PREPARING FUTURE TEACHERS FOR PROFESSIONAL ACTIVITY THROUGH HISTORICAL THINKING. (Scientific journal of the Fergana State University, 2023)
This article is about the mechanisms of preparing future teachers for professional activities through historical thinking, and the professional and spiritual worldviews of future pedagogues who are studying in the field of pedagogy today are matured on the basis of historical thinking. Also, the issues of conducting the professional components of future teachers as a representative of the field that plays an important role in the development of our country are not only related to science, but closely connected with historical thinking and historical consciousness.